Ethnomathematics in Batik Making Activities in Saung Baswet, Banjarsari Wetan Village, Banyumas - Rahmasari; Alfika, Shofa (International Journal of Research in Mathematics Education, 2023)
Abstract: Ethnomathematics is a discipline that explores the relationship between culture and mathematics. In Indonesia, one culturally rich tradition is batik. The process of creating batik involves various stages that result in diverse motifs unique to each region. The aim of this research is to identify the ethnomathematical aspects related to the practice of batik-making, the batik motifs, and to analyze the mathematical concepts associated with batik. The research employs a qualitative ethnographic approach. Data is collected through interviews, observations, and documentation, and is subsequently analyzed using data collection methods, data reduction, data presentation, conclusion drawing, and verification. In the process of batik-making at Saung Baswet Village, Banjarsari Wetan, Banyumas, various mathematical activities such as calculations, measurements, designing, and motif placement are discovered. Some mathematical concepts revealed in batik motifs include points, lines, angles, as well as geometric transformations such as translation, rotation, reflection, and dilation. Additionally, there are concepts related to plane figures such as right triangles, rectangles, trapezoids, circles, and polygons, as well as concepts of symmetry, similarity, and congruence.